Simultaneous activity of male and female gonads in intersex hermit crabs - Sant'Anna, Bruno Sampaio [UNESP]; Turra, Alexander; Zara, Fernando Jose [UNESP] (Inter-research, 2010)
Intersexuality in hermit crabs was investigated using anatomical, histological and electron-microscopy techniques, with Clibanarius vittatus as a model. The specimens were collected in the intertidal zone of Pescadores Beach, state of São Paulo, Brazil, and dissected to describe the anatomy of the reproductive organs. Different portions of the reproductive system were stained with hematoxylin and eosin, and the gonopore morphology was analyzed by scanning electron microscopy. The intersex individuals showed both male and female reproductive systems, with ducts that are connected to the gonopores. The morphology of the gonopores was similar in males and females. The intersex individuals also developed functional male and female gonads in the same individual. These observations confirmed that intersex hermit crabs can reproduce as males or females, thus supporting the hypothesis that they may be part of a true sequential hermaphroditic process.
Keywords: Intersexuality; Hermaphroditism; Hermit crab; Protogyny; SEM; Histology; Morphology